2020
DOI: 10.24167/psidim.v19i2.2856
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Riot Police Officers: Emotional Regulation and Five Trait Personality as Predictor

Abstract: This study examines the role of emotional regulation and five trait personality towards burnout. Personality consists of five types, namely openness, agreeableness, extraversion, conscientiousness and neuroticism. Emotional regulation consists of cognitive reappraisal and expressive suppression. Burnout consists of emotional exhaustion, personal accomplishment, and depersonalization. The subjects were riot police officers from Jakarta Regional Police. The sampling methods used were purposive sampling and conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…If there are complaints that indicate depersonalization, then that is an early indication that the employee is experiencing work fatigue. The same thing was conveyed by Wahyuni and Dewi (2020) in their research findings, where five significant personality traits were proven to have an on work fatigue with a contribution of 70.90 percent. Employee fatigue can be seen through their attitude towards the individuals served.…”
Section: The Effect Of Personality On Work Fatiguesupporting
confidence: 54%
See 1 more Smart Citation
“…If there are complaints that indicate depersonalization, then that is an early indication that the employee is experiencing work fatigue. The same thing was conveyed by Wahyuni and Dewi (2020) in their research findings, where five significant personality traits were proven to have an on work fatigue with a contribution of 70.90 percent. Employee fatigue can be seen through their attitude towards the individuals served.…”
Section: The Effect Of Personality On Work Fatiguesupporting
confidence: 54%
“…Employee burnout arises because of the large amount of work to be done while the ratio of employees in the company is relatively limited, so that employees must handle workloads that exceed their abilities and experience mental and emotional exhaustion. Likewise Wahyuni and Dewi (2020) who stated in their research findings that five personality traits significantly influence burnout. Work fatigue among employees can be seen from the attitude of employees towards the people they serve.…”
Section: Personality and Work Fatiguementioning
confidence: 94%
“…The findings of this study become an exciting reference concerning law enforcement that must be implemented, where everyone is equal before the law and in any situation, the law must be enforced, [2]; [24]; [1]; [25]; [26].…”
Section: Effect Of Job Burnout On Resiliencementioning
confidence: 99%
“…Recent studies on Covid 19 that review job stress and work stress have an impact on police performance, including; [2]; [3]; [4]; [5] revealed that the Covid 19 pandemic greatly affected the level of psychological health in the form of anxiety, behaviour problems, panic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Н. Widhiastuti вважає, що особливості емоційної сфери відіграють провідну роль у вирішенні проблем, котрі можуть впливати на психічне здоров'я особистості [13]. P. Wahyuni та F. Dewi наголошують на значущій ролі емоцій у професійній діяльності поліцейських, яка характеризується складністю та напруженістю [12]. L. Schaible та M. Six зазначають, що поліцейська діяльність є стресовою професією, яка призводить до безлічі несприятливих наслідків.…”
Section: роль емоцій у професійній діяльності поліцейських із різним ...unclassified